IbM KELOMPOK USAHA MAKANAN RINGAN BERBAHAN DASAR POTENSI LOKAL KABUPATEN PURWOREJO - Dewi Shanti Nugrahani, Galuh Aditya, Hesti Respatiningsih & (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
This activity aims at empowerment and development of snack business based on local potency. Mitra is a group of Micro small and Medium Enterprises community of Ganesha (KUB Bahtera) Purworejo and culinary group of Angudi Laras Purworejo (KBU Satu Hati). There are 8 participants. Problems faced by partners include: Lack of marketing access, low production capability, low access to capital for funding, Low financial management capability and business accounting administration, Limited human resources marketing and Production. To solve these problems, the program solutions offered are: 1) Increased marketing access, 2) Improvement of product processing techniques, 3) Strengthening of loan access to various funding sources, 3) improvement of financial management and business administration, and 4) Strengthening Partnership. The method used is training and mentoring. The results achieved are: the increasing ability of participants in the field of online marketing, enhancement of capabilities in designing product packaging, increasing sales through the implementation of online marketing, and strengthening the partnership relationship between groups.Keyword: snacks, business groups, online marketing